The Analysis of the Main Character's Speaking Strategies in Struggling against Alzheimer - Heru Susanto; Dwijani Ratnadewi (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2017)
The process of determining the possible intention or purpose of Aliceâ€™s utterances is decipherable by applying politeness theory, particularly positive politeness strategy proposed by Brown and Levinson (1987) as the main approach. The way she performs her efforts or struggle are mostly stated by using optimistic strategy which aims to ensure her interlocutor that she is â€œstill Aliceâ€ who has outstanding intelligence and brightness and considered as a high flying academic carrer woman. It is shown through the modal verb â€œcanâ€ which expresses her abilities to conduct her activities and the tobe â€œam/isâ€ that illustrates her conviction in delivering statements. It means that she builds and performs the optimism to maintain everything which has been accumulated by herself. Promise and giving understanding strategy are also used to portray the way she faces and survives on her Alzheimer. In promise strategy, it is shown through the modal verb â€œwillâ€ which indicates that she has a high intention to do something. While, in giving understanding strategy, it can be seen from innovative ways applied by herself. Although she has a disease which usually gets worse over time, but she tries hard with kinds of way to conquer it. Based on the previous description, there are some significances about positive politeness strategy in language. It is not only a strategy that is used to utter or assert a statement but it is also able to reveal the hidden meaning of the speaker. Therefore, by using positive politeness strategy, people can detect what actually desired by the speaker. In this research, this strategy is used by Alice because she wants to show that she tries hard for struggling against her Alzheimer. It is conducted by Alice as she does not want that the Alzheimer hold a rein on herself which can limit her abilities, break her carrer, and also affect the harmony of her family.Â Â